2020
DOI: 10.1002/1878-0261.12769
|View full text |Cite
|
Sign up to set email alerts
|

KDM3A/Ets1 epigenetic axis contributes to PAX3/FOXO1‐driven and independent disease‐promoting gene expression in fusion‐positive Rhabdomyosarcoma

Abstract: Abbreviations shRNA, short hairpin ribonucleic acid; qRT-PCR, quantitative reverse transcription-polymerase chain reaction; IVIS, in vivo imaging system; KD, knock down.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…The transcriptional activity of ets1 has been reported to be regulated by epigenetic modifications (Liu et al 2020;Sobral et al 2020). The present study represented an association between KMT5A and ets1 (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…The transcriptional activity of ets1 has been reported to be regulated by epigenetic modifications (Liu et al 2020;Sobral et al 2020). The present study represented an association between KMT5A and ets1 (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…A significant positive correlation between KDM5A and ETS1 was confirmed in PRAD tissues. ETS1 has been found to be activated by KDM3A through epigenetic regulation (Sechler et al 2017; Sobral et al 2020). Importantly, we observed that KDM5A knockdown in cells led to an increase in H3K4me2 expression whereas a decline in ETS1 expression, indicating that KDM5A enhances ETS1 expression through the demethylation of H3K4me2.…”
Section: Discussionmentioning
confidence: 99%